(untitled) (Bangladesh Journal of Medical Education, 2017)
Background: Bachelor of dental surgery course curricula need to be constantly analyzed and evaluated in order to offer dental courses in accordance with current technical innovations of dentistry as well as the demands of community oral health. Under the assumption that it is important to comprehend some students’ perceptions, the present study aims to analyze students’ perceptions regarding dental courses, embracing the academic environment, and describe the current scientific published literature about this research object. Specifically, it aims to access and synthesize the scientific knowledge involving students’ perceptions regarding dental courses, by means of constructing thematic categories classifying its levels of evidences. Objectives: The present study was undertaken to identify the teachers and students perception about the present status of undergraduate dental curriculum in Bangladesh. Methods: This descriptive type of cross sectional study was conducted in seven public and private dental colleges of Bangladesh after getting written permission from the principal of the respective dental colleges. Voluntary participation of the students was ensured and the names of the students’ as well as teachers were kept confidential. The teachers and students of final years from the different dental colleges were the study population; among them four hundred (400) students and one hundred twenty teachers (120) were taken as sample by convenient sampling. Data collection instrument was a semistructured questionnaire with 5-point Likert scale with maximum score 5 and minimum score1for final year students’ and in depth interview was used for teachers. Results: 87% teachers mentioned that the total hours for practical/clinical classes in individual subject are inadequate. 63 % teachers mentioned that the total hours for lecture classes in individual subject are inadequate. The overall results regarding the competency acquired by the newly passed dental graduate from the BDS course was satisfactory but some problematic areas were highlighted which interfered in achieving their satisfaction on their competencies Conclusion: In this study, the students reported that they have acquired greater practical and clinical experiences in few areas from the curriculum of BDS course. The majority of the students were not satisfied on their acquired competencies in most of the areas after their graduation. This was due to shortage of course duration in comparison to number of subjects and contents, improper distributions of the subjects, inadequate duration of community placement, less allocation of hours in practical and clinical classes etc. According to their opinion, lack of supervision and feedback in the clinical class, improper method of clinical assessment system of the students in all level are the responsible factors so that the students were not satisfied with the overall undergraduate BDS curriculum. Bangladesh Journal of Medical Education Vol.7(2) 2016: 28-33